Observations of Electron Vorticity and Phase Space Holes in the Magnetopause Reconnection Separatrix. Issue 8 (22nd August 2022) - Ahmadi, Narges; Eriksson, Stefan; Newman, David; Andersson, Laila; Ergun, Robert E.; Wilder, Frederick D.
Abstract: We report Magnetospheric Multiscale (MMS) observations of two electron vortices with a roughly 10 km or 2–3 electron skin depths cross‐section across the magnetospheric separatrix of a dayside magnetopause reconnection structure. The enhanced electron vorticity, which is caused by a significant velocity shear in the electron flows streaming in opposite directions along northward‐directed magnetic field lines, leads to perturbations perpendicular to the reconnecting magnetic field on the order of 1–2 nT. The high electron vorticity periods are also associated with electron phase space holes having the largest bipolar parallel electric field amplitudes ∼25 mV/m observed across this exhaust. Less intense ∼10 mV/m electron phase space holes propagate along a northward magnetic field away from the X‐line within a northward reconnection exhaust. The electron phase space holes with the largest bipolar parallel electric fields are observed to propagate toward the X‐line within discrete channels of southward and super‐Alfvénic 1, 500 km/s electron flows in the magnetospheric separatrix layer. Key Points: We observe enhanced electron vorticity at an earthward separatrix of magnetopause reconnection The electron vorticity causes perturbations in the magnetic field There is correlation between large amplitude phase space holes and enhanced vorticity in the dayside reconnection separatrix